EXPLORING THE ROLE OF KISWAHILI AND MALAGASY LANGUAGE IN EDUCATION: LINGUISTIC BRIDGES IN EAST AND SOUTHERN AFRICA - Florette, Rasolonirina; Augustin, Ravaoarisoa Simonette; Emynorane, Ralaivao Hanginiaina (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
This study explores the role of Kiswahili and Malagasy in education, examining how these languages serve as linguistic bridges in East and Southern Africa. Focusing on Tanzania and Madagascar, the study uses a qualitative approach to investigate the perspectives of students and lecturers at universities in both countries. By conducting in-depth interviews with key informants, the study highlights the cultural, educational, and social significance of Kiswahili in Tanzania and Malagasy in Madagascar, shedding light on their influence in higher education settings. The findings reveal the importance of these languages not only in fostering communication and academic success but also in promoting regional integration and cultural identity. The study underscores the challenges and opportunities these languages present in the context of multilingualism and educational development in East and Southern Africa. Through the voices of students and educators, the study contributes to understanding how Kiswahili and Malagasy function as tools for knowledge dissemination and intercultural exchange in the region.